Géneros de la memoria: retórica de la narración en la épica y la historiografía latinas - Lorenzo, Juan (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2011)
In this paper we propose a way of approaching the genres of historiography and of epic from the rhetoric doctrine about the narratio and about the objectives that any literary text can aim at - docere, mouere, delectare. By applying this double criterion, and not taking into account whether the text is written in prose or verse, it is possible to approach the concepts of ‘history’ (as the narration of events that have taken place and whose main purpose is docere) and of ‘epic’ (as the narration of fictional facts –except in the case of historical epic- which seeks above all delectatio). And it is also possible to find out what these two genres have in common and what differences exist between them